Acessibilidade ao sistema de transporte público por ônibus: indicadores para Regional Administrativa Barreiro, Belo Horizonte-MG - Antonio Henrique Noronha Ribeiro (2024)
The rapid process of urbanization experienced in Brazil, especially from the mid-20th century onwards, was driven by the late industrialization process, which reorganized productive and economic forces, significantly transforming the spatial distribution of the population and shaping the dynamics of the urban territorial arrangement. However, the urban configuration in the country is marked by socially and spatially uneven development, often accompanied by the spatial peripheralization of poverty. One of the direct consequences relates to mobility and accessibility barriers for significant portion of the population, directly linked to the precarity of public transportation systems. Apparently, peripheral areas of major urban and metropolitan centers, such as the Barreiro Administrative Region in Belo Horizonte, suffer from the inefficiency of the bus public transportation system, resulting in long and time-consuming journeys, as well as high fares. Considering that improvements in accessibility to public transportation represent a way to reduce inequalities, enabling more people to access opportunities, this research proposes the development of indicators of public bus transportation accessibility in the Barreiro Administrative Region, systematized in three dimensions: accessibility to bus boarding stops, accessibility to the public bus transportation system, and accessibility through the public bus transportation system. The indicators were conceived based on data from the 2012 OD Survey, the 2010 Census, and BHTrans/PBH. The results indicate significant inequalities in access to the bus transportation system, revealed not only by the overall accessibility index. In many cases, this low accessibility coincides with the system's ridership, especially for low-income populations. Based on the investigation of accessibility conditions, the results of this research provide potentially useful data that can assist decision-making in transportation projects and public policies, especially in areas marked by socio-economic challenges and inadequacies in transportation services.